How to Deal With Multi-Proxy Data for Paleoenvironmental Reconstructions: Applications to a Holocene Lake Sediment Record From the Tian Shan, Central Asia - Schroeter, Natalie; Toney, Jaime L.; Lauterbach, Stefan; Kalanke, Julia; Schwarz, Anja; Schouten, Stefan; Gleixner, Gerd (Frontiers in Earth Science, 2020)
Multi-proxy investigations on geological archives provide valuable information about environmental variations in the past. As opposed to single-proxy studies, the combination of several proxies can reveal more detailed information and strengthen subsequent paleoenvironmental reconstructions. However, there is still no consensus about how to deal with resulting highly dimensional datasets in a statistical manner. In many cases, the interpretations of multi-proxy datasets rely on visually matching several proxy records, which can lead to incorrect or insufficient interpretations. Here we report an innovative approach that combines the novel dimension reduction technique Uniform Manifold Approximation and Projection (UMAP) and the time series analysis R package asdetect to identify and characterize Holocene environmental phases and phase boundaries in a sediment core from Lake Chatyr Kol, southern Kyrgyzstan. Despite the fact that the Holocene climate evolution of Central Asia has been intensively studied during the last decades, knowledge about regional climate development during the Holocene and the underlying mechanisms is still relatively scarce. We particularly focus on phase transitions and differentiate between event-based shifts as opposed to gradual phase transitions. For this study, long-chain alkenones were used as a paleotemperature proxy and variations in long-chain alkyl diol distributions were ascribed to relative changes of algal input. The compound-specific stable hydrogen isotope compositions (δD) of individual n-alkanes were utilized as paleohydrological proxies, with the δD of mid-chain n-alkanes reflecting changes in the δD of the lake water and the δD of long-chain n-alkanes recording the δD of the meteoric water. We show the potential of modern analysis tools for data-driven paleoenvironmental reconstructions and advocate for their more frequent implementation in multi-proxy studies.